PENGARUH PERSEPSI HARGA, KUALITAS PRODUK, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA ANAK PANAH KOPI TEMBALANG - Nugroho, Dwiki Setyo; Hayuningtias, Kristina Anindita (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2025)
This study explores the extent to which price perception, product quality, and promotional efforts influence consumer purchasing decisions at Anak Panah Kopi Tembalang. A total of 100 visitors of the coffee shop were recruited based on specific criteria through purposive sampling. The collected data were analyzed using a multiple linear regression method to examine the influence of each independent variable. The results indicate that price perception and promotion significantly and positively affect consumer purchasing decisions, while product quality does not show a significant effect. Among the three factors, promotion was found to have the strongest influence. These results highlight the importance of implementing effective promotional strategies to encourage consumer purchases and enhance business sustainability in an increasingly competitive environment.